2018
DOI: 10.1021/acs.energyfuels.8b00819
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Hydrogen-Enriched Biogas by Dry Oxidative Reforming with Nickel Nanopowder Using Response Surface Methodology

Abstract: Today, the worldwide research is focused on the development of alternative energy sources for power generation; thus, the present study aims to optimize the dry oxidative reforming (DOR) process parameters for H 2 -enriched biogas production by integrating response surface methodology with a three-level, three-factor Box−Behnken design in the presence of commercial Ni nanopowder. First, the effect of CH 4 /CO 2 and O 2 /CH 4 ratios on the catalytic performance of DOR was assessed in the temperature range of 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These findings suggest that when surplus steam is delivered to the autothermal reformer, the net heat requirement from the reactions increases. [ 43,44 ] The oxidation becomes more prominent as the O/E ratio rises, and the temperature of the autothermal reformer rises as well, until it reaches its ideal condition, where the hydrogen content reaches its maximum value. Table 5 lists a few near‐optimal parametric conditions for negligible heat requirement in ATR to produce H 2 from 702 simulation runs.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that when surplus steam is delivered to the autothermal reformer, the net heat requirement from the reactions increases. [ 43,44 ] The oxidation becomes more prominent as the O/E ratio rises, and the temperature of the autothermal reformer rises as well, until it reaches its ideal condition, where the hydrogen content reaches its maximum value. Table 5 lists a few near‐optimal parametric conditions for negligible heat requirement in ATR to produce H 2 from 702 simulation runs.…”
Section: Resultsmentioning
confidence: 99%
“…By doping or forming an alloy, the adsorption of O* at the Co step is regulated, and the oxidation of the Co catalyst can be inhibited . It has been reported that low Ni loading is sufficient to improve the performance of the catalyst when the catalyst is reduced at higher temperatures . Ni–Co/TiO 2 catalysts with a small amount of Ni substitution for Co can inhibit the oxidation of metallic Co, while too much Ni substitution can cause severe carbon deposition, implying that Ni–Co bimetallic catalysts with high DRM activity require a suitable Co/Ni ratio .…”
Section: Ni-early Transition Metalmentioning
confidence: 99%
“…184 It has been reported that low Ni loading is sufficient to improve the performance of the catalyst when the catalyst is reduced at higher temperatures. 194 Ni−Co/TiO 2 catalysts with a small amount of Ni substitution for Co can inhibit the oxidation of metallic Co, while too much Ni substitution can cause severe carbon deposition, implying that Ni−Co bimetallic catalysts with high DRM activity require a suitable Co/Ni ratio. 195 Takanabe et al 184 found that the Ni/ Co ratio could modulate the surface metal properties to obtain highly active and durable DRM catalysts.…”
mentioning
confidence: 99%
“…Meanwhile, in order to reduce energy requirement and catalyst carbon deposition in the DR process, another approach, that is, dry oxidative reforming (DOR), has been investigated for syngas production 21,28 . Extensive research articles were published on experimental studies, with some on catalyst preparation using different oxides and promoters, their reaction mechanisms, and performances in DOR 29–31 . DOR uses both CH 4 and CO 2 as reactants and O 2 as an additional oxidant to minimize carbon deposition on the catalyst and make an overall energy‐efficient process.…”
Section: Introductionmentioning
confidence: 99%